Best Practices for Early Bystander Intervention Training on Workplace Intimate Partner Violence and Workplace Bullying - Lassiter, Barbara J. (Journal of interpersonal violence, 2021)
The purpose of this study was to gain consensus from experts on the best practices that might be taken into account when developing early bystander intervention training programs to reduce both workplace intimate partner violence (WIPV) and workplace bullying (WB). A U.S. nationwide panel of 17 experts completed the qualitative five-round modified Delphi study. The experts were leaders or managers from business, government, not-for-profit, and academic organizations who exceeded the criteria to participate in the study. Research included the collection of data electronically to answer the research question: What do experts with experience in the area of workplace violence (WV), WB, or WIPV agree constitute the best practices that might be considered when developing a bystander training program to address WIPV or WB? In Rounds 1 and 2, participants provided their demographics and initial opinions about best practices. Likert-type scales were used as follows: Round 3, to rate agreement about which statements constituted best practices; Round 4, to rank order statements from Round 3; and Round 5, to rate the importance of each statement. Results were analyzed for top best practices. Three themes emerged: leadership, training, and people involved in the incident. Findings indicated that senior management must be committed to lead the way; that victims, targets, and bystanders need to be protected, and confidentiality must be maintained. The study was based on the concept of altruism and empathy that humans show to others experiencing crisis or suffering. Practical implications showed a clear emphasis on the critical need for leadership as the foundation for reducing all forms of violence in the workplace; training should instruct staff in how to identify WV, WB, and WIPV, when to intervene, and how to get help; and ensure that victims are treated in a supportive and caring manner.